Profile of Pediatric Central Nervous System (CNS) Tumor Patients at Dr. Soetomo General Academic Hospital Surabaya in 2017-2023 - Wirawan, Putu Tanisya Putri; Fauziah, Dyah; Suryaningtyas, Wihasto; Gunawan, Prastiya Indra (Syntax Corporation, 2025)
Central nervous system (CNS) tumors are a heterogeneous group in any region of the brain and spinal cord. They causes significant morbidity and mortality. CNS tumor is diagnosed based on clinical and radiological findings, but a definitive diagnosis requires histopathology examination. However, the demographic and histopathological profile of pediatric CNS tumor is rarely studied in Indonesia. The study aims to analyze the profiles of pediatric CNS tumor patients based on demographic and histopathological characteristics. This retrospective descriptive study was conducted using secondary data from a medical records of all pediatric CNS tumor patients at Dr. Soetomo General Academic Hospital from January 2017 to December 2023. The results show a total of 165 cases were included in this study, 60% occurred in male and 40% in female. The majority of the patients aged 5-8 years old (30.3%) and tumors commonly located within posterior fossa (21.4%). WHO grade I pilocytic astrocytoma (24.2%) is the most common histopathological subtype for benign CNS tumors followed by WHO grade IV medulloblastoma (20.6%) for malignant CNS tumor. Thus, pediatric CNS tumor was found to be more frequent in males than females, with the peak occurring in 5-8 years old. The most common location was within posterior fossa. The most common histopathological subtype was WHO grade I pilocytic astrocytoma.